On the Astronomical Significance of Stone Number 137 of Zorats Qarer Megalithic Monument - Malkhasyan, H. A.
The work is dedicated to discovering a new type of “observational device” in the Zorats Qarer megalithic monument and uncovering a new layer of the continuous function of the monument using the “new device.” The possible use of the “new device” significantly differs from the observation platforms and angular stones in the same monument. Stone No. 137 in question was previously considered a ”periscope” based on some assumptions. By examining the astronomical and structural application of the mentioned stone in more detail and without preconceived assumptions (or with much simpler, obvious suppositions), new functions of its application are revealed. One relates to the observations of circumpolar stars in the direction of the stone hole. The other relies on the puddle and the special structure of the stone. The latter makes it possible to determine the days of the equinoxes and the summer solstice due to the Sun’s positions. By combining these two functions, the probable date of the use of the stone is determined: 15500 BC, when it was possible to observe the appearance of the star γ Cygni (Sadr, Swan constellation) after sunset on the summer solstice in the direction of the hole. Thus, a new layer of the “calendar observations” (15500 BC) is added to the already identified layers (9000, 5800, and 2341 BC), which is in harmony with the logic regarding this and other similar monuments (for example, Göbekli Tepe) and essentially complements the evolutionary chain of ancient cultural concepts with its content and time.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture